Independence of the Central Bank of West African States :An Expected Reform? - (:unkn) unknown (My University, 2007)
Why increase the independence of the Central Bank of West African States? The answer can be sought in the monetary and institutional evolution of the West African Economic and Monetary Union. The advantage would be to increase confidence in the value of the currency and to guarantee the continuity of the economic and monetary integration of West Africa. The feasibility of the reform implies strengthening the collegiality of monetary decisions and the transparency of the management of the Central Bank. It is also necessary to improve the coordination of budgetary and monetary policies, with a view to a stronger and more regular growth of the economies of the Union.
Keywords: African Research